Changes induced by diet with different concentrations of resistant starch in the metabolism of carbohydrates and lipids in Wistar rats (Research, Society and Development, 2021)
This study aimed to evaluate the effect of replacing pregelatinized starch with resistant starch on the metabolism of lipids and carbohydrates in male Wistar rats. 20 male rats were divided into two groups, which received a diet with 9.5% (DAP) and 18.1% (DAR) of resistant starch for 22 days. Weight, feed, and water consumption were analyzed and the concentrations of cholesterol and triglycerides in serum and muscle and hepatic and muscle glycogen were quantified. The data were analyzed by Tukey's test (p>0.05) and box-plot graphs. There were no significant differences in feed and water intake, but the animals in the DAP group showed an increase in weight (51.12g to 55.27g) while those in the DAR group decreased (49.01g to 44.15g). The DAR group showed a decrease in triglycerides, total serum cholesterol (from 125.761 mg/dL to 104.874 mg/dL), and muscle glycogen, but an increase in triglycerides in the gastrocnemius muscle compared to the DAP group (from 0.160 mg/dL to 0.259 mg/dL). These results point to a decrease in the glucose absorption speed in the group of animals with a diet with a higher amount of resistant starch, which may have induced a decrease in the processes of synthesis of triglycerides and cholesterol leading to an increase in catabolism of these substrates by the body, plastic adaptation of muscles for the use of fatty acids in their oxidative metabolism.